2015
DOI: 10.1080/10408398.2015.1077193
|View full text |Cite
|
Sign up to set email alerts
|

High intensity pulsed electric field as an innovative technique for extraction of bioactive compounds—A review

Abstract: How to extract bioactive compounds safely and efficiently is one of the problems for the food and pharmaceutical industry. In recent years, several novel extraction techniques have been proposed. To pursue a more efficient method for industrial production, high intensity pulsed electric field (HIPEF) extraction technique has been developed. HIPEF extraction technique, which is based on the conventional pulsed electric field (PEF), provided higher electric field intensity and a special continuous extraction sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…In PEF applications, high voltages (kV range) are applied in pulses of short duration (nano or micro-seconds) with the main objective of causing electro-permeabilization and destroying the cell membranes to accelerate the extraction rate [ 91 ]. PEF is used extensively for the extraction of phenolic compounds from terrestrial plants [ 92 , 93 , 94 ]. There is very limited information on the application of PEF marine resources, however, since the method is proven to be effective for the extraction of phenolic compounds from land plants, it should also be replicated for the extraction of marine phenolics, including seaweeds.…”
Section: Emerging Technologies For Extraction Of Marine Phenolicsmentioning
confidence: 99%
“…In PEF applications, high voltages (kV range) are applied in pulses of short duration (nano or micro-seconds) with the main objective of causing electro-permeabilization and destroying the cell membranes to accelerate the extraction rate [ 91 ]. PEF is used extensively for the extraction of phenolic compounds from terrestrial plants [ 92 , 93 , 94 ]. There is very limited information on the application of PEF marine resources, however, since the method is proven to be effective for the extraction of phenolic compounds from land plants, it should also be replicated for the extraction of marine phenolics, including seaweeds.…”
Section: Emerging Technologies For Extraction Of Marine Phenolicsmentioning
confidence: 99%
“…PEF employs very high voltage pulses (1 to 80 KV/cm) for fractions of a second such as millisecond or microsecond; the voltage and the treatment duration can be adjusted according to the requirements. Besides microbial inactivation, PEF is also applied for alternative purposes such as enzyme inactivation (Onwude et al, 2017), and to increase extraction yield (Puértolas & Martínez De Marañón, 2015;Yan, He, & Xi, 2017). In relation to proteins, PEF has been noted to alter the structural features of proteins; for example, a PEF treatment of 35 KV/cm for 40 μs induces vibrational changes on the bonded side of amino acid chains, altering β-sheets and β-turns suggesting the denaturation of the protein (Liu, Zeng, Deng, Yu, & Yamasaki, 2011).…”
Section: Novel Processing Techniquesmentioning
confidence: 99%
“…A large number of studies have been devoted to this issue and showed that PEF-pretreatment represents a promising green alternative method for different applications, such as diffusion extraction, osmotic treatment, pressing extraction, drying and freezing. Besides increasing the mass transfer, PEF-assisted processing showed other advantages as compared to conventional ones, with improvement of extraction yields, decrease of processing time, decrease of process intensity (temperature, solvent…), and reduction of heat-sensitive compounds degradation (11, 52, 108, 109). The important features of moderate PEF treatment, as compared to other green alternative methods, are the possibility of pore resealing after treatment and the formation of different pore sizes in electroporated cell membrane depending on PEF conditions.…”
Section: Eco-friendly Extraction and Valorization Of Bioresourcesmentioning
confidence: 99%